Association of specific HLA alleles in patients with interstitial cystitis suggesting autoimmunity - Tabansky Stern, Inna; Wang, Jiayao; Moldwin, Robert M.; Kim, Jason M.; Singh, Jason H.; Tran, Derek C.; Najjar, Souhel; Akinci, Melis; Howard, Alexis; Duke-Cohan, Joseph E.; Belhaj, Marwa; Stevens, Jonathan; et al. (Frontiers in Molecular Medicine, 2025)
Interstitial cystitis/bladder pain syndrome (IC/BPS) with Hunner Lesions (Hunner Type Interstitial Cystitis or HIC) is characterized by lesions on the bladder wall. Previous work on these lesions identified B cells and monocytes within the lesion. However, the overall role of the adaptive immune system in the disorder remains uncertain. In this study, we performed HLA sequencing on 12 IC/BPS patients with HIC and 7 Non Hunner Type IC (NHIC) patients, and identified HLA-DQB1*02:02 and HLA-DRB1*07:01:01 have a significant association with HIC. This pilot study provides genetic evidence supporting a potential autoimmune component in HIC and may help define the pathogenesis of at least one subtype of IC/BPS, and lay the groundwork for identifying the etiology of IC/BPS as a disease complex. Identifying the mechanisms can also open new approaches to treatment. Identifying an HLA haplotype associated with HIC would indicate that it is autoimmune.